Days Ending in Why - Martin, Julia (Université d'Ottawa / University of Ottawa, 2015)
In DAYS ENDING IN WHY, interdisciplinary artist Julia Martin identifies the schism of her autobiographical practice: deep melancholia and absurd irony. The fragmentation of the works presented knowingly resist cohesion, instead, through their arrangements and the potentials of space between them, they carry on conversations with one another. Rooted in the personal narrative, the works span across multiple mediums; photography, film, installation/sculpture, and literature. Martin emphasizes both the tragic and the comedic, pacing the show as a play between the two. Also, there are cats. So many cats.
Keywords: Visual Art; Fine Art; Narrative; Story; Photography; Fragments; Memory; Trauma; Dark humour; Mourning; Melancholia; Grief; Loss; Vignette